Evaluation of Bacillus thuringiensis and flubendiamide for controlling Metisa plana via aerial spraying in oil palm plantation - Che Ahmad Hafiz Che Manan,; Siti Noor Hajjar Md Latip,; Ayman Che Razali,; Syed Mazuan Syed Mohamed,; Cik Mohd Rizuan Zainal Abidin, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
Bagworm, Metisa plana (Lepidoptera: Psychidae) is one of the most serious and critical pests on oil palm. Aerial spraying is a treatment method that is used to control infestation especially in the large outbreak areas. Flubendiamide and Bacillus thuringiensis kurstaki (Btk) as potential environmentally friendly pesticide were chosen for the study based. Aerial spraying with aircraft of both pesticide were carried out at an oil palm plantation. Four plots: A, B, C and D were chosen; each plot measuring 20ha. The aim of this study is to evaluate the effective spray volume for Flubendiamide and to determine cost-effectiveness between Flubendiamide and B. thuringiensis kurstaki (Btk). Both Flubendiamide spray volume of 30 and 50 liters ha-1 successfully reduced 100% the population from 196 bagworm per frond (BPF) to 0 BPF at 68 days after treatment (DAT) for 30 liters ha-1 and from 266 BPF to 0 BPF at 68 DAT for 50 liters ha-1. Application at 30 liters ha-1 of Flubendiamide were proven cost effective according to the cost benefit ratio (BCR). However, 50 liters ha-1 of Btk showed slight reduction in first treatment but increased the population to 195% from 99 BPF to 294 BPF at 68 DAT. Flubendiamide spray was proven to be more cost effective than Btk according to cost benefit ratio (BCR). Therefore, it is recommended for the management to use Flubendiamide with aerial spraying method for successive control of bagworm population below the economic threshold level (ETL).